Guilda de abelhas coletoras de óleo (APOIDEA) associada à Byrsonima sericea e Byrsonima cydoniifolia (Malpighiaceae) - Lua, Shantala (2013)
Floral oil-collecting bees have close relations with Malpighiaceae species. This study aims to characterize the bee guilds that visit two Byrsonima (Malpighiaceae) species and investigate if the variation in floral oil supply influences on the richness and local abundance of these bees in an area in Chapada Diamantina. Bees were collected using entomological nets during the visit to Byrsonima and the floral oil supply was estimated at 12 transects through the Byrsonima spp density and the amount of oil available per flower and per plant. A large variation in Byrsonima spp density was detected among the 12 transects sampled what resulted in differences in floral oil supply among transects (1320.4g-16397.2g). The sample was 638 individuals belonging to 34 Apoidea species, being 24 species components of the floral oil-collecting bee guild. Centridini was the tribe with the largest representation of species richness and in abundance. The richness and abundance of Centridini were positively correlated to both Byrsonima spp density and the amount of oil estimated to each transect. However, the richness and abundance of Tapinotaspidini and Tetrapediini didn’t correlate to Byrsonima spp density or the amount of oil estimated to each transect.